THE EFFECT OF USING QUESTION ANSWER RELATIONSHIP (QAR) STRATEGY ON STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT AT ELEVENTH GRADE OF SMA SWASTA PABAKU STABAT - Dwi Widyantari; efrini panjaitan; Ismail Ismail (STKIP Budidaya Binjai, 2022)
The objective of this study is to find out The Effect of Using Question Answer Relationship (QAR) Strategy on Students’ Reading Comprehension of Narrative Text at Eleventh Grade of SMA Swasta PABAKU Stabat. This study is an experimental research with the population is all students of class XI at SMA Swasta PABAKU Stabat as many as 60 students from 2 classes, as control class is XI-IPA 1 and the experimental class is XI-IPA 2. The instrument of this research is using pre-test and post-test with multiple choice question consist of 20 questions. After the calculation of the data knowing the mean obtained by the respondents in the control class is 67,5 and the mean of data in experimental class is 86,83. It can be concluded that students’ reading comprehension achievement in the experimental class is good. Based on the calculation of validity test, it can be concluded that the data has valid. Then based on the calculation of reliability of test, found that the data has reliable. Based on the calculation of normality, it can be concluded that the distribution of data is normal. After testing the data hypothesis criteria that have been obtained in the control class and the experimental class, it has been found that the hypothesis is received, where tcount > ttable = 4,4 > 1,67155. So it can be concluded that Question Answer Relationship (QAR) Strategy affected on Students’ Reading Comprehension of Narrative Text at Eleventh Grade of SMA Swasta PABAKU Stabat.